Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Bakso Granat Mas Azis Cabang Bukit Lama Palembang - Riri Hanifa; Noprian; Saudi Berlian (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This research intends to analyze the effect of service quality (X), on guest satisfaction (Y) at Bakso Granat Mas Azis. This research is quantitative and data dissemination through questionnaires. The sample from this research is reached 88 respondents, which means the questionnaire is distributed to 88 people. The data collection technique used is slovin method, The data analysis method used is multiple linear regression analysis with the help of SPSS (Service Product and Service Solution) version 25. The results of this research indicate that partially and simultaneously (together)service quality (X), has a positive and significant impact onguest satisfaction (Y) at Bakso Granat Mas Azis.